1999
DOI: 10.1016/s0006-3495(99)77392-3
|View full text |Cite
|
Sign up to set email alerts
|

External Tetraethylammonium As a Molecular Caliper for Sensing the Shape of the Outer Vestibule of Potassium Channels

Abstract: External tetraethylammonium (TEA+) blocked currents through Kv1.1 channels in a voltage-independent manner between 0 and 100 mV. Lowering extracellular pH (pHo) increased the Kd for TEA+ block. A histidine at position 355 in the Kv1.1 channel protein (homologous to Shaker 425) was responsible for this pH-dependent reduction of TEA+ sensitivity, since the TEA+ effect became independent of pHo after chemical modification of the Kv1.1 channel at H355 and in the H355G and H355K mutant Kv1.1 channels. The Kd values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…TEA has been used as a molecular caliper to probe the inner pore of Kv channels (27). TEA could be used in the same way for K Ca 2 channels, but first, it had to be determined whether apamin and TEA bound to non-overlapping sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEA has been used as a molecular caliper to probe the inner pore of Kv channels (27). TEA could be used in the same way for K Ca 2 channels, but first, it had to be determined whether apamin and TEA bound to non-overlapping sites.…”
Section: Discussionmentioning
confidence: 99%
“…TEA can therefore be used as a "molecular caliper" to probe the dimensions of the inner pore under different conditions. Different sensitivities are proposed to indicate differences in pore structure and dynamics (26,27). Fig.…”
Section: The His Residue In the Outer Pore Turret Also Contributed Tomentioning
confidence: 99%
“…We were intrigued that perhaps this novel isoform might refine our understanding of the pharmacological as well as physiological properties of the channel. To test whether the pore region of SK3 channels is affected by the 15 amino acid insertion, we tested different blockers that are known to bind at the outer vestibule, such as TEA ϩ (Bretschneider et al, 1999), d-tubocurarine, apamin (Ishii et al, 1997), and ScTX ). The S5-P-loop-S6 regions of SK2 and SK3 channels differ only at the residues Val485 and His521, which correspond to Val47 and Val95 in the KcsA channel and Tyr415 and Val451 in the Shaker potassium channel.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the TEA ϩ block was identical for both isoforms. For Kv1.1 channels, it has been shown that the TEA ϩ binding is close to the selectivity filter within the P-loop region (Yellen et al, 1991;Bretschneider et al, 1999). Because this region is not interrupted by the inserted amino acids in hSK3_ex4, the TEA ϩ binding sites of hSK3_ex4 would be assumed not to be affected by the insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Nothing is known about modulation of K ϩ channels specifically by norbornane and similar groups. Catechol in concentrations above 0.1 mM has been used widely to inhibit native K ϩ currents (Ito and Maeno, 1986;Erdelyi and Such, 1988;Kuenzi and Dale, 1998;Bretschneider et al, 1999;Hess and El Manira, 2001); however, the mechanism of its action remains unknown. Our data on catechol inhibition of cloned Kv channels indicate that the site of catechol action is different from that of 48F10, suggesting that 48F10 may constitute a novel pharmacophore for K ϩ channels (manuscript in preparation).…”
Section: Figmentioning
confidence: 99%